Single‐Stage Optimized Microwave‐Induced Activated Carbon from Coconut Shell for Cadmium Adsorption - Yusop, Mohamad Firdaus Mohamad; Mohd Johan Jaya, Erniza; Mohd Din, Azam Taufik; Bello, Olugbenga Solomon; Ahmad, Mohd Azmier (Chemical engineering & technology, 2022)
The toxicity of heavy metals motivated the synthesis of coconut shell‐based activated carbon (CSAC) through single‐stage microwave irradiation technique to scavenge cadmium ions (Cd(II)). Response surface methodology revealed the optimum radiation power and radiation time which translated into 85.45 % of Cd(II) removal and 41.78 % of CSAC's yield. Isotherm and kinetic data were best described by Freundlich and pseudo‐first‐order (PFO) models, respectively. The changes of enthalpy, entropy, and activation energy were determined as well as the reduction of CSAC yield and Cd(II) removal after six regeneration cycles. Conversion of coconut shell into activated carbon (AC) to remove Cd(II) ions from wastewater was successfully optimized by using response surface methodology with radiation power and radiation time as variables. The optimized coconut shell‐based AC (CSAC) was verified in terms of isotherm and kinetic behavior. Regeneration study showed that CSAC can withstand the regeneration cycles multiple times.